2015
DOI: 10.1186/s13020-015-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Centipeda minima (Ebushicao) extract inhibits PI3K-Akt-mTOR signaling in nasopharyngeal carcinoma CNE-1 cells

Abstract: BackgroundCentipeda minima (Ebushicao) has been used for the treatment of various diseases, such as nasal allergies, rhinitis and sinusitis, nasopharyngeal carcinoma, cough, and headache. This study aims to investigate the anticancer activities of Centipeda minima ethanol extracts (CME) against nasopharyngeal carcinoma cell CNE-1 and their underlying mechanism.MethodsCNE-1 cells were treated with different concentrations (15–50 μg/mL) of CME for different time intervals (24, 48, and 72 h). Cytotoxicity of CME … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…As is known to all, Akt/mTOR signaling pathway participates in multiple cellular functions, including cell survival, differentiation, and autophagy [ 20 ].The Akt/mTOR signaling pathway could negatively regulate autophagy through Akt phosphorylation, following by promoting phosphorylation and activation of mTOR [ 21 , 22 ]. Notably, SMI-4a could down-regulate the phosphorylation level of Akt and mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…As is known to all, Akt/mTOR signaling pathway participates in multiple cellular functions, including cell survival, differentiation, and autophagy [ 20 ].The Akt/mTOR signaling pathway could negatively regulate autophagy through Akt phosphorylation, following by promoting phosphorylation and activation of mTOR [ 21 , 22 ]. Notably, SMI-4a could down-regulate the phosphorylation level of Akt and mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described (22,27), Centipeda minima was collected in August 2010 in Xiangfan, Hubei Province, China (latitude, 32 • 04 ′ N; longitude, 112 • 05 ′ E), and authenticated by Prof. Sibao Chen based on morphological features. A voucher specimen (EBSC-016-09) was deposited at the herbarium of the State Key Laboratory of Chinese Medicine and Molecular Pharmacology, Department of Applied Biology and Chemical Technology, The Hong Kong Polytechnic University.…”
Section: Plant Materials and Sample Preparationmentioning
confidence: 99%
“…Reports suggest that Centipeda minima extracts (CME) possess anti-inflammatory (17), anti-bacterial (18,19), and anti-allergic (20) effects. Previous studies have demonstrated the anti-cancer effects of CME, and compounds extracted from CM, in various cancers including nasopharyngeal carcinoma (13,14,21,22), leukemia (23), glioblastoma (24), lung cancer (25), and colon cancer (26), however, the effects of CME on breast cancer have to date, not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…How to reduce the toxicity and side effects of anti-cancer drugs has become a major problem that we need to solve urgently. In recent years, the research on the prevention and treatment of NPC by traditional Chinese medicine is popular year by year, and these traditional Chinese medicines have achieved satisfactory results [2][3][4].…”
Section: Introductionmentioning
confidence: 99%